2019
DOI: 10.1097/ico.0000000000002148
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Fluorescein Tear Breakup Time Test in Dry Eye

Abstract: Purpose-To examine the effect of volume and method on fluorescein tear breakup time (TBUT) values, and to evaluate test efficacy in an independent sample free of selection bias.Methods-Subjects were assessed using a battery of dry eye tests. Efficacy study: subjects were randomized to the Dry Eye Test (DET), Standard Strip (SS) and liquid NaFl, on separate days. A masked examiner measured TBUTs from video recordings. Verification study: Subjects were investigated for efficacy using volumes of 5.0 and 2.0 μl mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Although non-invasive TBUT (NIBUT) has been recommended for the measurement of TBUT [ 16 ], FBUT is still widely used in clinical practice due to its simplicity. A recent study confirmed that FBUT has valid diagnostic accuracy [ 17 ]. In addition, when FBUT is tested, simultaneous judgment of FBUPs can be performed.…”
Section: Introductionmentioning
confidence: 84%
“…Although non-invasive TBUT (NIBUT) has been recommended for the measurement of TBUT [ 16 ], FBUT is still widely used in clinical practice due to its simplicity. A recent study confirmed that FBUT has valid diagnostic accuracy [ 17 ]. In addition, when FBUT is tested, simultaneous judgment of FBUPs can be performed.…”
Section: Introductionmentioning
confidence: 84%
“…However, it is susceptible to factors such as environment, filter paper and examinee, which can easily lead to false-positive or false-negative results of misdiagnosis and misjudgment. 6 At present, there are still some shortcomings in the diagnosis and treatment of dry eye syndrome in China, mainly manifested in the following aspects: (1) Diagnostic standards are not uniform. 15 (2) The treatment of dry eye is more confusing.…”
Section: Discussionmentioning
confidence: 99%
“…5 In recent years, there are various diagnostic methods for dry eye syndrome, but it is currently the focus of attention to seek a diagnostic method that has both high practical value and economical. 6…”
Section: Introductionmentioning
confidence: 99%
“…The subject blinked naturally three times 2 and the mean of three measurements recorded. Subjects were considered to have dry eye disease if the mean TBUT was ≤6.0 seconds 7 or Level 2 severity.…”
Section: Methodsmentioning
confidence: 99%